COMPLEXITY OF THE MEANINGS OF MEANING - Milal, A. Dzo’ul; Fi’aunillah, Tristy Kartika; Swasono, Endratno Pilih (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This paper attempts to explore the complexity of the meanings of meaning. As the core content of language, meanings exist in the most essential organ of human beings, i.e. the mind. The origin of language started with the existence of human awareness. Its presence has resulted from interaction between human beings and their social and natural environments. In communication, meanings are wrapped in forms where their relation is not necessarily linear. Meanings are referential, ideational, representational, implicational, metaphorical, and/or intentional. One form may convey several meanings, and one meaning can be expressed in various forms. The intervening variable determining such a phenomenon is context. Hence, to perceive meanings, one must understand words and structures, cultures, and surrounding linguistic and non- linguistic contexts.